HLA‐DPB1*04:01 Protects Genetically Susceptible Children from Celiac Disease Autoimmunity in the TEDDY Study. (June 2015) - Hadley, David; Hagopian, William; Liu, Edwin; She, Jin‐Xiong; Simell, Olli; Akolkar, Beena; Ziegler, Anette‐G; Rewers, Marian; Krischer, Jeffrey P; Chen, Wei‐Min; Onengut‐Gumuscu, Suna; Bugawan, Teodorica L; et al.
Abstract : OBJECTIVES: Tissue transglutaminase autoantibodies (tTGAs) represent the first evidence of celiac disease (CD) development. Associations of HLA‐DR3‐DQA1*05:01‐DQB1*02:01 (i.e., DR3‐DQ2) and, to a lesser extent, DR4‐DQA1*03:01‐DQB1*03:02 (i.e., DR4‐DQ8) with the risk of CD differ by country, consistent with additional genetic heterogeneity that further refines risk. Therefore, we examined human leukocyte antigen (HLA) factors other than DR3‐DQ2 for their contribution to developing tTGAs. METHODS: The Environmental Determinants of Diabetes in the Young (TEDDY) study enrolled 8, 676 infants at an increased HLA‐DR‐DQ risk for type 1 diabetes and CD into a 15‐year prospective surveillance follow‐up. Of those followed up, 21% ( n =1, 813) carried DR3‐DQ2/DR3‐DQ2, 39% ( n =3, 359) carried DR3‐DQ2/DR4‐DQ8, 20% ( n =1701) carried DR4‐DQ8/DR4‐DQ8, and 17% ( n =1, 493) carried DR4‐DQ8/DQ4. Within TEDDY, a nested case–control design of 248 children with CD autoimmunity (CDA) and 248 matched control children were genotyped for HLA‐B, ‐DRB3, ‐DRB4, ‐DPA1, and ‐DPB1 genes, and the entire cohort was genotyped for single‐nucleotide polymorphisms (SNPs) using the Illumina ImmunoChip. CDA was defined as a positive tTGA test at two consecutive clinic visits, whereas matching in those with no evidence of tTGAs was based on the presence of HLA‐DQ2, country, and sex. RESULTS: After adjustment for DR3‐DQ2 and restriction to allele frequency (AF) ≥5%, HLA‐DPB1*04:01 was inversely associated with CDA by conditional logistic regression (AF=44%, odds ratio=0.71, 95% confidence interval (CI)=0.53–0.96, P =0.025). This association of time to CDA and HLA‐DPB1*04:01 was replicated with statistical significance in the remainder of the cohort using imputation for specific HLA alleles based on SNP genotyping (hazard ratio=0.84, 95% CI=0.73–0.96, P =0.013). CONCLUSIONS: HLA‐DPB1*04:01 may reduce the risk of tTGAs, an early marker of CD, among DR3‐DQ2 children, confirming that additional variants in the HLA region influence the risk for CDA.